2019
DOI: 10.4067/s0718-34292019000200021
|View full text |Cite
|
Sign up to set email alerts
|

No-till broccoli farming over pearl millet: weed suppression and yield at consecutive seasons in the southern coast of Brazil

Abstract: No-till broccoli farming over pearl millet: weed suppression and yield at consecutive seasons in the southern coast of BrazilCultivo de brócoli cero labranza sobre mijo perla: supresión de malezas y productividad en períodos consecutivos en la costa sur de Brasil ABSTRACT The pearl millet is a potential feedstock for biomass production under sensitive areas to climate changes, as the southern coast of Brazil. Looking for the sustainability of small-scale vegetable farmers on that region, the aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
2
1
Order By: Relevance
“…The significant effect of pearl millet organic mulch on weed suppression in broccoli was consistent with the results of Grisa et al (2019), who demonstrated the potential of this species for the ecological management of weeds. The sunn hemp mulch also had suppressive effect on weed biomass only at 30 DATr of broccoli; however, by 50 DATr, a considerable increase in weed biomass had occurred.…”
Section: Weed Establishment In the Broccoli Cropsupporting
confidence: 89%
See 2 more Smart Citations
“…The significant effect of pearl millet organic mulch on weed suppression in broccoli was consistent with the results of Grisa et al (2019), who demonstrated the potential of this species for the ecological management of weeds. The sunn hemp mulch also had suppressive effect on weed biomass only at 30 DATr of broccoli; however, by 50 DATr, a considerable increase in weed biomass had occurred.…”
Section: Weed Establishment In the Broccoli Cropsupporting
confidence: 89%
“…With regard to the variable effect of glyphosate in the broccoli trial, these results highlighted the resilience of broccoli to grow and produce without herbicide sprayed on flattened cover crops, which is consistent with the finding of Grisa et al (2019), who reported great efficacy of pearl millet in suppressing weeds in broccoli.…”
Section: Broccoli Growth and Yieldsupporting
confidence: 87%
See 1 more Smart Citation
“…Crotalaria juncea and millet plants have been shown in the past decades to exert strong suppression of invasive plants while promoting high soil coverage and canopy light capture (8,10,16). In addition to the physical factors, chemical factors are also involved in the suppression of weeds by cover plants.…”
Section: Introductionmentioning
confidence: 99%
“…Among the characteristics that must be considered when choosing the appropriate species of cover plants, the rapid establishment, tolerance to water deficit, production of phytomass, suppression of weeds and the ability to recycle and release nutrients for crops in succession have to be considered (Marcante et al, 2011;Teixeira et al, 2011;Hirata et al, 2014). As it has such characteristics, pearl millet (Pennisetum glaucum L.) (Grisa et al, 2019) was the species selected for this work.…”
Section: Introductionmentioning
confidence: 99%